Postcolonialism and the Study of the Middle Ages - Altschul, Nadia R. (History compass, 2008)
This article focuses on the use of postcolonial criticism in the study of the European Middle Ages. It concentrates on two issues critiqued in particular by historians: anachronism and applicability. The article is thus structured around two questions: Why should medievalists explore contemporary postcolonial issues instead of strictly medieval ones? And why should the tools of postcolonial theory be considered applicable to medieval societies and times?